Genetic barcoding and phylogenetic analysis of dusky cotton bug (Oxycarenus hyalinipennis) using mitochondrial cytochrome c oxidase I gene - Khan, A. Z.; Amad, I.; Shaheen, S.; Hussain, K.; Hafeez, F.; Farooq, M.; Noor Ul Ayan, H. (Cellular and Molecular Biology, 2017)
Cotton dusky bug (Oxycarenus spp.) mostly attack on cash crops such as Gossypium, Cola and Hibiscus which affect the national economy therefore sustainable pest management is needed. Cytochrome c oxidase I (COI) gene is utilized as marker gene for DNA barcoding, genetic and ecological study of insects. In present study insect (cotton dusky bug) samples were collected from cotton fields in Faisalabad. COI gene was amplified from genomic DNA of bug and cloned into pTZ57R/T vector (Fermentas). The clone was sent to Macrogen (South Korea) for Sanger sequencing. The phylogenetic analysis and pairwise multiple sequence alignment showed that our cotton dusky bug grouped with two species of Oxycarenus genus and highest sequence identity was 91.1% with Oxycarenus hylinipennis. This is the first report of genetic barcode of Oxycarenus hylinipennis from cotton from Pakistan.